Local Soviets of People’s Deputies of the BSSR during the Soviet perestroika (1985–1991): the crisis of growth - Elizarov, Sergey A. (Journal of the Belarusian State University. History, 2024)
The process of changing the role of the Councils of People’s Deputies of the BSSR during the period of perestroika policy is considered. Attention is focused on local Councils of People’s Deputies (regional, district and city) and their executive committees. It is shown that in 1985–1987 the measures taken by the union and republican authorities and administration corresponded to the expectations of the leadership of local Soviets of People’s Deputies and provided for a gradual increase in the role of local authorities and administration in the Soviet political and economic system. It is noted that only in 1988, as a result of another attempt to delineate powers between the Communist Party and government bodies, the first measures were taken to radically change the role of the Councils of People’s Deputies and their accelerated transformation into independent and responsible local authorities and management. It is emphasised that in the context of growing crisis phenomena in the economy, growing dissatisfaction of the population with the results of perestroika, the expansion of powers of the Councils of People’s Deputies led to the spread of localism, ignoring state interests and a decline in executive discipline. As a result, a project was developed for the actual introduction of a state of emergency, which involved abandoning the democratic paradigm of reorganising the public administration system as a dangerous and destructive experiment for society. Radical and accelerated transformation of the system of state power and administration in Belarus in the late 1980s – early 1990s ended in failure.